Rock Glacier relitti e antica distribuzione del permafrost nel Gruppo Adamello Presanella (Alpi centrali) - SEPPI R; BARONI C.; CARTON, ALBERTO (2010)
The current and the past lower limit of permafrost has been estimated in the Adamello Presanella Group (Central Alps, Italy) using a rock glacier inventory. The inventory was based on aerial photographs analyses and field surveys. In the inventory, a total of 216 rock glaciers have been reported and described, and 128 of these are regarded as relict landforms. These rock glaciers have a flat morphology, a gently sloping frontal scarp and a surface characterized by several cavities. In most cases their surface is covered by dense vegetation, and often their front reach the present tree line. The distribution of active/inactive landforms allows to estimate a lower limit of discontinuous permafrost presently located at about 2500 m a.s.l., an altitude 430 m higher than that suggested by the relict landforms. No chronological data exist in this region about the age of the relict rock glaciers. Nevertheless, a visual comparison with the Late Glacial extent of glaciers, as provided by a map obtained from the moraines geometry, allows to estimate an age no older than the Late Glacial Gschnitz stage for the most of them (87 on 128). Since the lower boundary of discontinuous permafrost is located at an altitude corresponding with the MAAT (Mean Annual Air Temperature) of -1/-2°C, the difference in MAAT that coincides with the difference in elevation between the fronts of active/inactive and relict rock glaciers can be estimated using the vertical temperature lapse rate calculated for this mountain group (0.59°C/100 m). The altitudinal difference between the fronts of active/inactive and relict rock glaciers coincides with a difference of about 2.5°C in the MAAT. This difference reduces to about 2.4°C on northern slopes and increases to about 2.7°C on southern slopes. This data gave us an estimate of the MAAT difference between the Late Glacial (when the presently relict rock glaciers were active) and the present day.